A Two-Dimensional Unsteady FDTD Model for Radon Transport with Multiple Sources Emanation from Soil Layers - H. Bezzout; E. H. El Ouardy; N. Meskini; H. El Faylali (National Research and Innovation Agency, 2023)
A two-dimensional numerical model for radon transport based on the finite difference time domain (FDTD) method have been developed. The model is governed by the radon transport equation taking into account the mechanisms of diffusion, advection, and decay. The purpose of this model is to simulate the evolution of radon concentration which can be influenced by various parameters including depth and diffusion coefficient of the soil layer plus the velocity and initial concentration of radon. The obtained results were compared to an analytical solution to demonstrate the ability of this model for predicting the spatio-temporal evolution of radon transport in the porous media of soil layers.